Editor's Choice – Risk of Major Amputation Following Application of Paclitaxel Coated Balloons in the Lower Limb Arteries: A Systematic Review and Meta-Analysis of Randomised Controlled Trials. (January 2022) - Katsanos, Konstantinos; Spiliopoulos, Stavros; Teichgräber, Ulf; Kitrou, Panagiotis; Del Giudice, Costantino; Björkman, Patrick; Bisdas, Theodosios; de Boer, Sanne; Krokidis, Miltiadis; Karnabatidis, Dimitrios
Abstract : Objective: There have been concerns about the long term safety of paclitaxel coated devices in the lower limbs. A formal systematic review and meta-analysis of randomised controlled trials (RCTs) was performed to examine the long term risk of major amputation using paclitaxel coated balloons in peripheral arterial disease (PAD). Method: This systematic review was registered with PROSPERO (ID 227761). A broad bibliographic search was performed for RCTs investigating paclitaxel coated balloons in the peripheral arteries (femoropopliteal and infrapopliteal) for treatment of intermittent claudication or critical limb ischaemia (CLI). The literature search was last updated on 20 February 2021 without any restrictions on publication language, date, or status. Major amputations were analysed with time to event methods employing one and two stage models. Sensitivity and subgroup analyses, combinatorial meta-analysis, and a multivariable dose response meta-analysis to examine presence of a biological gradient were also performed. Results: In all, 21 RCTs with 3 760 lower limbs were analysed (52% intermittent claudication and 48% CLI; median follow up two years). There were 87 major amputations of 2 216 limbs in the paclitaxel arms (4.0% crude risk) compared with 41 major amputations in 1 544 limbs in the control arms (2.7% crude risk). The risk of major amputation was significantly higher for paclitaxel coated balloons with a hazard ratio (HR) of 1.66 (95% CI 1.14 – 2.42; p  = .008, one stage stratified Cox model). The prediction interval was 95% CI 1.10 – 2.46 (two stage model). The observed amputation risk was consistent for both femoropopliteal ( p  = .055) and infrapopliteal ( p  = .055) vessels. Number needed to harm was 35 for CLI. There was good evidence of a significant non-linear dose response relationship with accelerated risk per cumulative paclitaxel dose (chi square model p  = .007). There was no evidence of publication bias ( p  = .80) and no significant statistical heterogeneity between studies ( I 2  = 0%, p  = .77). Results were stable across sensitivity analyses (different models and subgroups based on anatomy and clinical indication and excluding unpublished trials). There were no influential single trials. Level of certainty in evidence was downrated from high to moderate because of sparse events in some studies. Conclusion: There appears to be heightened risk of major amputation after use of paclitaxel coated balloons in the peripheral arteries. Further investigations are warranted urgently.